THE ROLE OF DIGITAL LEADERSHIP IN ORGANIZATIONS TO IMPROVE EMPLOYEE PERFORMANCE AND BUSINESS SUCCESS - Ito Turyadi; Zulkifli Zulkifli; Muhamad Risal Tawil; Helmi Ali; Abdurrahman Sadikin (SEAN Institute, 2023)
Digital transformation has become an integral component of the business world in the rapidly advancing digital age. Organizations must employ digital technologies effectively in order to remain relevant and competitive in the global marketplace. Digital leadership is crucial for managing change and influencing employee performance and business success as a whole. Utilizing digital technologies to lead, manage, and influence employees and business processes constitutes digital leadership. Digital leaders promote innovation, collaboration, and information accessibility. Digital leadership can increase efficiency, productivity, and innovation in the workplace by adopting the appropriate digital technologies. Digital leadership also contributes to the success of a business by facilitating change management, promoting digital transformation, and making sound decisions. Research indicates that digital leadership facilitates improved employee performance, the development of digital skills, and the achievement of business objectives. In an ever-changing digital era, digital leadership is not only the leader's responsibility, but also a shared responsibility.